Physiotherapy service providers' views on issues of assistants: Are physiotherapy assistants needed? - M. Wazakili; R. M. B. Mpofu (AOSIS, 2000)
This paper presents views of physiotherapy service providers in selected areas of the Western Cape Metropolitan Region, over the issue of physiotherapy assistants and whether they are needed. Data were collected through semi-structured interviews. A thematic analysis resulted in five pre-determined categories. While the participants agreed that assistants are needed, they had divergent views over issues of name and role of assistants. The lack of both standardised training for assistants and knowledge of delegation by professionals was highlighted. The training of assistants should be examined seriously if the shortage of physiotherapy services in general has to be alleviated, suggesting that the recommendations of the national qualification framework (NQF) should be applied to the training of physiotherapists together with the assistants.